2022
DOI: 10.3389/fenvs.2022.895646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Several Organic Fertilizers on Heavy Metal Passivation in Cd-Contaminated Gray-Purple Soil

Abstract: Soil heavy metal pollution has become a major ecological and environmental problem and a serious threat to global food security. Organic fertilizer can not only improve soil quality and provide nutrients for plants but also reduce the harm of heavy metal ions to a certain extent, meaning it has become a current research hotspot in the field of heavy metal passivation. In this paper, a completely combined experimental design was used to compare the effects of five organic fertilizers [nutshell organic fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Bentonite is a 2:1 clay mineral with montmorillonite as the main component. Previous research has shown that the addition of bentonite increased the C concentration in each aggregate size class [27]. Previous studies by our research team have also confirmed that a one-time application of bentonite in semi-arid areas could improve soil structure, preserve soil water, and effectively increase the SOC concentration and stock capacity of sandy soil [28,29].…”
Section: Introductionsupporting
confidence: 80%
“…Bentonite is a 2:1 clay mineral with montmorillonite as the main component. Previous research has shown that the addition of bentonite increased the C concentration in each aggregate size class [27]. Previous studies by our research team have also confirmed that a one-time application of bentonite in semi-arid areas could improve soil structure, preserve soil water, and effectively increase the SOC concentration and stock capacity of sandy soil [28,29].…”
Section: Introductionsupporting
confidence: 80%
“…However, optimum degradation temperature can vary according to metal types, for instance, Cd bio-degradation by Bacillus jeotgali was maximum at 35°C while bio-degradation by the same bacteria was higher at 30°C ( Chanmugathas and Bollag, 1988 ). The adsorption efficiency is also affected by soil organic matter, for instance, organic matter tends to fix the metals in soil which reduces the availability to metals ( Wang et al., 2022 ). A short-term study investigates the response of different temperatures (5, 15, and 25oC) Cd, Cu, Pb, and Zn removal by Carex pseudocyperus , C. riparia , and Phalaris arundinacea .…”
Section: Factors Affecting the Bioremediation Processmentioning
confidence: 99%